A Retrospective Analysis of Nursing Students' Clinical Experience in an All-Male Maximum Security Prison. Issue 4 (July 2018) - Bouchaud, Mary T.; Brooks, Madeline; Swan, Beth Ann
Abstract : Prisons provide an ideal learning experience to prepare prelicensure students with the knowledge and skill set needed for practice in the 21st century. Beginning descriptive evidence demonstrates that correctional health is an innovative community resource to educate nursing students in today's changing model of health care delivery and practice. This article shares results from a retrospective analysis of the perceptions and experiences of nursing students during their community clinical rotation in an all-male maximum security prison.